2020
DOI: 10.3390/molecules25204864
|View full text |Cite
|
Sign up to set email alerts
|

The Function and Mechanism of Lipid Molecules and Their Roles in The Diagnosis and Prognosis of Breast Cancer

Abstract: Lipids are essential components of cell structure and play important roles in signal transduction between cells and body metabolism. With the continuous development and innovation of lipidomics technology, many studies have shown that the relationship between lipids and cancer is steadily increasing, involving cancer occurrence, proliferation, migration, and apoptosis. Breast cancer has seriously affected the safety and quality of life of human beings worldwide and has become a significant public health proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 155 publications
1
35
0
Order By: Relevance
“…In recent years, great achievements have been made in abnormal lipid metabolism in tumors. 12 , 19 Lipid molecules with the diagnostic potential for BRCA are constantly being discovered. 12 , 52 Studies have found that the abnormal lipid metabolism of BRCA cells is closely related to their resistance to HER2 inhibitors and CDK4/6 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, great achievements have been made in abnormal lipid metabolism in tumors. 12 , 19 Lipid molecules with the diagnostic potential for BRCA are constantly being discovered. 12 , 52 Studies have found that the abnormal lipid metabolism of BRCA cells is closely related to their resistance to HER2 inhibitors and CDK4/6 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“… 10 In addition to being a component of the cell membrane and a source of energy storage, lipids can also activate cell proliferation, differentiation, and migration, as well as induce cell death. 11 , 12 Abnormal lipid metabolism has been reported to be related to the occurrence and development of a variety of malignant tumors, such as prostate cancer, 13 ovarian cancer, 14 pancreatic cancer, 15 liver cancer, 16 and BRCA. 17 Studies have found that changes in lipid metabolism exist during the early stages of BRCA development, and a lipid-rich environment promotes the proliferation and migration of BRCA cells.…”
Section: Introductionmentioning
confidence: 99%
“…They play a key role in many biological processes since they can act as energy reservoir, signal molecules, protein traffickers and of course main constituents of plasma membranes ( Gross and Han, 2011 ). Many diseases (such as cancer, diabetes, cardiovascular diseases) and pathological conditions are often accompanied by lipid dysregulation ( Lydic and Goo, 2018 ; Guo et al, 2020 ). Initially included in metabolomics, the importance of this field, linked to the physicochemical specificities of these compounds, to their very huge number and to their essential biological role quickly led to the appearance of a distinct approach called lipidomics ( Dennis, 2009 ).…”
Section: Nuclear Magnetic Resonance In Clinical Metabolomics and Personalized Medicinementioning
confidence: 99%
“…Giallourou and colleagues [71] showed that breast bacteria interfere with the biosynthesis of ceramide, cholesterol, oxidized cholesteryl esters, diacylglycerol, lysophosphatidylcholine, phosphatidylethanolamines, and phosphatidylcholines to modulate the lipid composition of tumors. Of note, cholesterol and lipid homeostasis also play a role [4,[114][115][116]. The widespread changes to the oncobiome metabolism suggest that the breast cancer oncobiome participates in the metabolic support of rapidly dividing breast cancer cells.…”
Section: Tumor Colonizationmentioning
confidence: 99%